PENDIDIKAN AGAMA ISLAM BEWAWASAN SPIRITUALITAS EKOLOGI: Telaah Materi dan Model Pembelajaran - Mohammad Muchlis Solichin (IAIN Ponorogo, 2017)
Abstract: Ecological Spirituality is an awareness for connecting the environment through education. Education is a means of shaping the character of the environmental awareness. The knowledge and awareness of the importance of the environment can be fostered through the process of learning in school/madarasah. Ecological Spirituality can be implemented in the Learning of Islamic Education (PAI) by integrating the concept of Islam which is related to the environment into the teaching. This paper focus on 1) What are the learning materials of Islamic Religious Education (PAI) associated with ecological spirituality?, 2) How is the implement of the learning model of Islamic Religious Education (PAI) with associated with ecological spirituality. The findings revealed that the PAI learning materials which is related to the ecological spirituality comprising the learning of environment in the perspective of Alquran, Hadith, Fiqh, Aqidah, Moral and History of Islamic Culture. Meanwhile, the learning models encompassing a contextual learning, thematic learning and, inquiry learning models.الملخص: إن الروحانية الإيكولوجية هو الوعي للقدرة على التعامل مع البيئة، وأن ينمّى هذا الوعي – بقدر المستطاع – عن طريق التربية. والتربية هي الوسيلة لتكوين طبيعة الاهتمام والوعي بالبيئة. ويكون الفهم عن الوعي بالبيئة يمكن تنميته عن طريق عملية التعليم في المدارس. والروحانية الإيكولوجية يمكن تكوينها عن طريق عملية التربية الإسلامية ببيان التعاليم الإسلامية المتعلقة بالبيئة والعالم. وتركيز هذا المقال هو: 1) ما هي المواد في التربية الإسلامية في ضوء الروحانية الإيكولوجية: 2) كيف تطبيق نماذج التعليم في مادة التربية الإسلامية في ضوء الروحانية الإيكولوجية. ومن البيانات المجموعة يمكن الاستنتاج منها : أن مواد تعليم مادة التربية الإسلامية في ضوء الروحانية الإيكولوجية تحتوى على تعليم موضوع البيئة في ضوء القرآن والسنة والفقه والعقيدة والأخلاق وتاريخ الثقافة الإسلامية. وأما نماذج تعليم مادة التربية الإسلامية على ضوء الروحانية الإيكولوجية فهي : نموذج التعليم السياقي، ونموذج التعليم الموضوعي، ونوذج التعليم على أساس التحقيق. Abstrak: Spiritualistas Ekologi merupakan suatu kesadaran untuk mampu berhubungan dengan lingkungan yang ditanamkan melalui jalur pendidikan. Pendidikan merupakan wahana pembentukan karakter peduli terhadap lingkungan. Pemahaman, kesadaran akan pentingnya lingkungan alam dapat ditumbuhkembangkan melalui proses pembelajaran di sekolah/madarasah. Spiritualitas Ekologi dapat dilakukan melalui pembelajaran Pendidkan Agama Islam (PAI) dengan menjelaskan ajaran Islam berkaitan dengan lingkungan, alam. Fokus tulisan ini adalah 1) Apa saja materi pembelajaran Pendidikan Agama Islam (PAI) berwawasan spiritualitas ekologi, 2) Bagiamana pelaksanaan model-model pembelajaran Pendidikan Agama Islam (PAI) berwawasan spiritualitas ekologi. Dari penelusuran data, terungkap bahwa materi pembelajaran PAI berwawasan spiritualitas ekologi meliputi pembelajaran lingkungan hidup dalam perspektif Alquran, Hadis, Fiqh, Aqidah, Akhlak dan Sejarah Kebudayaan Islam. dan Akhlak. Sementara itu model-model pembelajaran (PAI) berwawasan spiritualitas ekologi, adalah model pembelajaran kontekstual, model pembelajaran tematik, dan model pembelajaran, inquiry.